Analysis of Solution Criminal Acts Theft Cases - Nur Suryani Siwi (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2022)
High unemployment rate in Indonesia causes more and more people to experience economic conditions around poverty line. This then causes crime in Indonesia tends to increase. Most common crime committed is theft. Motive for this theft was mostly economic insistence. Theft is not a serious crime, however, theft may be subject to criminal law. Theft can be divided into two, namely light theft and ordinary theft. There are some differences between two although boundaries should be noted. This study analyzed how judges adjudicate a theft case. Judge needs to pay attention to some points related to incriminating elements theft defendant. In this study research methods used are descriptive analytical and analyzed in accordance with secondary and primary data.